Making gains: the impact of outdoor residential experiences on students' examination grades and self-efficacy*. Issue 2 (15th March 2017) - Fuller, Carol; Powell, Daisy; Fox, Simon
Abstract: In this paper we explore the role of outdoor residential experiences on the sense of efficacy and examination attainment of a group of under achieving students from socially disadvantaged backgrounds. The article reports on a three year project which focuses on two groups of Year 9 (age 14) to Year 11 (age 16) students. The results reported here strongly suggest that the impact of these visits has been significant in terms of students' sense of confidence and efficacy and had a statistically significant impact on formal examination results in school. We conclude by suggesting that outdoor residential experiences have real educational value for those that take part and, given the evidence provided, believe this poses an interesting question as to whether the classroom should remain the primary site of learning because of the ways it develops positive outcomes within school.